Sexual and gender-based violence (SGBV) among protracted refugees in Nakivale refugee settlement, Uganda - Karooma, Cleophas; Murembe, Neema; Serwajja, Eria; Nakijoba, Veronica; Withaeckx, Sophie; Coene, Gily (My University, 2024)
Uganda’s refugee settlements are characterized by protracted refugees due to prolonged conflicts in neighbouring countries and the inability to find a lasting solution for the refugees. In these settlements, sexual and gender-based violence (SGBV) is widespread yet remains a silent affliction among women and girls, as well as men and boys, who are at an increased risk of multiple forms of SGBV as a result of protractedness. This empirical qualitative study carried out in Nakivale refugee settlement shows that prolonged stay has increased the vulnerability of the refugees to SGBV as it has created new forms of violence and exacerbated existing ones. The study findings further indicate that lack of durable solutions, especially the currently preferred resettlement, has contributed to protractedness and its related challenges. Sexual violence, intimate partner violence (IPV), and traditional harmful practices are the commonest forms of SGBV, and these have affected refugees’ health – physically, psychologically, and socially. Several interventions, including health, legal, psycho-social, safety and security, and economic empowerment, are reported to be in place to prevent and respond to the problem, but SGBV still exists, and many survivors and their families still conceal their SGBV experiences. The findings suggest that interventions aimed at creating awareness have helped in reducing SGBV cases. However, there are still gaps as some refugees are reluctant to report SGBV, and some still fabricate SGBV cases to meet the resettlement criteria. Protracted refugees should continuously be involved in measures for both prevention and response to SGBV for sustainability
Addressing gaps in knowledge and responses
Keywords: Sexual and gender-based violence (SGBV); Protracted refugees; Protractedness; Nakivale refugee settlement